A switching event-triggered resilient control scheme for primary and secondary levels in AC microgrids. (August 2022) - Shan, Yinghao; Pan, Anqi; Liu, Huashan
Abstract: In microgrid hierarchical control, primary control to stabilize system and secondary control to eliminate frequency/voltage deviations are both necessary for islanded microgrids. In this paper, a switching event-triggered (SET) resilient control scheme for microgrid primary and secondary levels has been proposed. First, droop control and model predictive control (MPC) are used for power sharing and driving signal generation respectively on primary level. An SET control method to trigger different MPC cost functions is proposed to balance output voltage quality and switching frequency. Then, distributed consensus and pinning control based method is used on secondary level. An SET mechanism to dynamically adjust secondary ratios to coordinate the transient deviation and response speed is proposed. Next, to deal with severe accidents, a resilient control scheme integrating primary and secondary levels is designed to maintain the system sound operation and improve the system immunity. Finally, the effectiveness of the proposed control scheme has been demonstrated by simulation with comprehensive scenarios. Highlights: Microgrids are typical complex cyber–physical systems that need to be regulated hierarchically. A switching event-triggered mechanism for triggering different cost function coefficients has been proposed for the model predictive controller in primary control. In secondary control, a switching event-triggered control method is also proposed for the dynamic adjustment of distributed secondary control ratios. To deal with severe accidents, a resilient control scheme that cooperates with primary and secondary controls is enabled.